Phase separation and mechanical behavior of AlCoCrFeNi-X (X = Cu, Mn, Ti) high entropy alloys processed via powder metallurgy - Oh, Min Chul; Sharma, Ashutosh; Lee, Hansung; Ahn, Byungmin (Intermetallics, 2021)
In this study, we investigated the phase separation behavior of AlCoCrFeNi-X (X = Cu, Mn, Ti) high-entropy alloys (HEAs) produced by mechanical alloying (MA) and spark plasma sintering (SPS). The microstructure, nanoindentation hardness, and elastic modulus of various phases were also studied to elucidate the relationship between chemical composition, crystal structure, and mechanical performance of the AlCoCrFeNi-X HEAs. The results indicate the formation of mixed phases: a face-centered cubic (FCC), and body-centered cubic (BCC) with ordered BCC (B2) precipitates formed in AlCoCrFeNi and AlCoCrFeNi-X (X = Cu, Mn). In addition, σ-phases were introduced in AlCoCrFeNi and AlCoCrFeNi–Mn. However, only BCC/B2 was observed in the AlCoCrFeNi–Ti HEA. The mechanical properties of the AlCoCrFeNi-X (X = Mn, Ti) alloys were superior to those of the AlCoCrFeNi–Cu alloy because of their higher BCC fraction, and the AlCoCrFeNi–Mn alloy exhibited superior strength because of the presence of a fine nanoscale BCC/B2 matrix coupled with high modulus and hard σ-phases. Thus, this study highlights that the microstructural and mechanical properties of AlCoCrFeNi HEAs can be tuned selectively via incorporation of suitable additive elements (X = Cu, Mn, Ti).
Keywords: Body-centred cubic; Chemical compositions; Crystals structures; Hardness and elastic modulus; High entropy alloys; Mechanical behavior; Nano-indentation hardness; Phase separation behavior; Phases transformation; Spark-plasma-sintering; High entropy alloy; Phase separation; Phase transformation; Powder metallurgy; Spark plasma sintering